I assume you mean 3y+2x+1. So sub in the points and see. The 1 is x and the -3 is y.
3(-3) + 2(1) + 1. Does this equal 0? -9+2+1 equals -6, so no, it is not a solution. For example, if your point is (1,-1), this would be a solution.If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656
x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656
6
no solution
There is one solution for x and one solution for y. The solution is: x = -1 ; y = 2
x = -1 y = 2 2x3 - 3xy = 2 (-1)3 - 3(-1)(2) = 2 (-1) - (-6) = -2 + 6 = 4 Suggestion: Please be careful around problems like this until you have some more experience.
It can be simplified in the form of: 2x3+9x2-7x-34 = 0
The solution is: x = 1 and y = -1
(x + y)3 + (x - y)3 = (x3 + 3x2y + 3xy2 + y3) + (x3 - 3x2y + 3xy2 - y3) = 2x3 + 6xy2 = 2x*(x2 + 3y2)
Agustín de Iturbide y Green died on 1925-03-03.
y = -2.5 is a equation. And solution to the equation is finding the value of the variable. If we see the equation y is already equal to -2.5 which is the solution to the equation.
In the equations Y=X-1 and Y=-X+1, the solution is (1,0)